Residents’ Perceived Landscape Benefits Can Help Extension Promote Good Landscape Management Practices - Laura A. Sanagorski Warner; Amanda D. Ali; Anil Kumar Chaudhary (EDIS, 2017)
Households can help conserve and protect water resources through irrigation and fertilizer best practices without compromising the quality of their landscape. UF/IFAS Extension, along with Extension services across the country, conducts programs to protect water quality and quantity by educating communities and individuals about research-based landscape practices (UF/IFAS, 2011). This four-page fact sheet describes the results of a survey that can help Extension promote good landscape management practices.